EFFECT OFWELLBORE HYDRAULIC TO CRITICAL RATE AND OPTIMUM RATE OF HORIZONTAL WELL IN RESERVOIR WITH THE BOTTOM WATER DRIVE - YANUARTO (NIM: 22208038), YOGI
Establishment of water cresting is a natural phenomenon that often occurs in horizontal wells (such as water coning in vertical well). Water cresting occurs when production of the well exceeds the critical production rate, where the critical flow rate is the minimum production rate that causes the stability of oil-water boundaries that change shape becomes unstable, which then water from the aquifer will flow vertically to form a cresting to the horizontal wells. The purpose of this research is to determine the effect of wellbore hydraulic against water cresting that occurs while starting production of the horizontal wells. Wellbore hydraulic pressure occurs because the ratio of pressure loss along the horizontal wells to pressure drawdown greater than 10%. This event is called finite conductivity where the influence of the horizontal wellbore hydraulic must be taken into account. The approach is to analyze the influence of several sensitivity variables with cresting performance using reservoir simulator. The sensitivity variables are the length of horizontal well, the distance from the WOC to perforation, permeability anisotropy, the density difference between water and oil also mobility. Afterward we gained some critical flow rate and optimum flow rate for each case, then by using Minitab, we obtain a multivariable regression equation that connect the influence of sensitivity variables to the optimum rate. The results showed that the permeability of the reservoir are generally large (> 1000 MD) has the characteristics of water cresting move to the point of heel of horizontal well, where the lowest pressure at this point. After calculating the ratio of pressure loss toward pressure drawdown for all sensitivity, resulting price is greater than 10%, this showed that the influence of wellbore hydraulic evidently indeed must be counted on. It also means that the greater of the ratio of pressure loss to pressure drawdown, oil earnings results will also be greater too. The price comparison of critical flow rate with several correlations shows that the simulation result from CMG gives the same graph.